EXPERIENCIA DE ESCUELAS SALUDABLES CON POBLACIÓN INDÍGENA Y AFROCOLOMBIANA EN EL DEPARTAMENTO DE CHOCÓ (2018)
Objective: a descriptive study of exploratory, who sought to account for the conditions of implementation of the Healthy Schools strategy in educational institutions of Choco Department and develop a model adapted to indigenous and Afro-Colombian population strategy was performed.Methods: collection, processing and analysis of information provided elements for the construction of the model: a participatory process, divided into two moments was performed.Results: strategy model Healthy Schools for indigenous and Afro-Colombian population, which proposes two routes one for educational institutions and another to generate intersectoral and interagency partnerships to promote healthy schools, each route contains five steps are designed in a participatory manner; additionally it was trained the participants in the proposed model.Conclusions: the Healthy Schools Strategy provides fundamental for human development, for health promotion in schools and thus to improve the quality of life of indigenous and Afro-Colombian communities elements.